Tumor clonality and resistance mechanisms in EGFR mutation-positive non-small-cell lung cancer: implications for therapeutic sequencing. (8th November 2018) - Kohsaka, Shinji; Petronczki, Mark; Solca, Flavio; Maemondo, Makoto
While the development of EGFR-targeted tyrosine kinase inhibitors (TKIs) has revolutionized treatment of EGFR mutation-positive non-small-cell lung cancer, acquired resistance to therapy is inevitable, reflecting tumor evolution. Recent studies show that EGFR mutation-positive non-small-cell lung cancer is highly heterogeneous at the cellular level, facilitating clonal expansion of resistant tumors via multiple molecular mechanisms. Here, we review the mechanistic differences between first-, second- and third-generation EGFR-targeted TKIs and speculate how these features could explain differences in clinical activity between these agents from a clonal evolution perspective. We hypothesize that the molecular dissection of tumor resistance mechanisms will facilitate optimal sequential use of EGFR TKIs in individual patients, thus maximizing the duration of chemotherapy-free treatment and survival benefit. Graphical abstract: